Positive Aspects Of Using The Competency-Based Approach To Improve Students’ Listening And Speaking Skills At Philological Institutions In South Korea And Finland (Zien Journal of Social Sciences and Humanities, 2025)
This article provides a comparative academic examination of the positive pedagogical effects of adopting the competency-based approach (CBA) for the advancement of listening and speaking skills in philological programs in South Korea and Finland. Both national systems possess distinct educational traditions yet share a commitment to aligning language education with global communicative demands. Drawing upon curriculum analyses, policy documents, and extant empirical studies, this investigation identifies core advantages associated with CBA implementation, including strengthened communicative competence, heightened learner autonomy, enhanced authenticity of instructional tasks, and more robust assessment frameworks. The analysis concludes that CBA contributes significantly to the professionalization of philological training by cultivating transferable communicative abilities essential for multilingual academic and occupational contexts.